Microstructure and Mechanical Properties of Aluminum Alloy Matrix Composite Reinforced with ZrO2 Particles - Baghchesara, M.A.; Abdizadeh, H.; Baharvandi, H.R. (Asian Journal of Chemistry, 2010)
Al-ZrO2 composites have found more applications in aerospace and automotive industries due to their higher tension and wear properties. One of the demanded methods in manufacturing these composites is vortex casting, because it is less expensive and covers large variety of materials and fabricating situations. In this research, a casting system was designed for manufacturing Al-ZrO2 composites in 5, 10 and 15 vol. % ZrO2 and 750, 850 and 950 °C casting temperatures. The resulting composites were tested for their mechanical properties and microstructure to study the effect of ZrO2 and temperature parameters. The results show enhanced mechanical properties. In this case the best sample (UTS = 232 MPa, H = 64 HB) was reached at 750 ºC and 15 % ZrO2 (from 145 Mpa and 43 HB, respectively). Generally it can be said that increasing ZrO2 vol. % and elevating melt temperature result in higher percent of porosities, uniform distribution of them and also increased segregation. By increasing ZrO2 % and shortening casting time, an enhanced distribution of ZrO2 particles can be achieved.